Expression of costimulatory molecules B7-1 (CD80), B7-2 (CD86), and interleukin 12 cytokine in multiple sclerosis lesions (The Rockefeller University Press, 1995)
Resting autoreactive T cells are present in the circulation of normal individuals without pathologic consequences. In autoimmune animal models, stimulation of these self-reactive T cells in the presence of costimulatory molecules B7-1 results in T cell-mediated autoimmune disease, whereas B7-2 stimulation generates regulatory autoreactive T cells that abrogate disease severity. Thus, reactivation in the brain of myelin-autoreactive T cells by antigen with costimulatory molecules may be a critical event in the pathophysiology of multiple sclerosis (MS), a putative autoimmune disease of central nervous system (CNS) myelin. We investigated the expression of cytokines and costimulatory molecules in a panel of 41 histologically characterized CNS specimens from 15 MS and 10 control cases using semiquantitative reverse transcriptase-polymerase chain reaction and immunocytochemistry. In four cases, vascular CNS infarcts with inflammation were compared with MS plaques from the same brain. We observed increased expression of B7- 1 and interleukin (IL) 12p40 in acute MS plaques, particularly from early disease cases but not in inflammatory infarcts. B7-1 staining was localized predominantly to the lymphocytes in perivenular inflammatory cuffs but not the parenchyma. In contrast, B7-2 was expressed predominantly on macrophages both in MS lesions of varied time duration and in inflammatory infarcts. These findings indicate that an early event in the initiation of MS involves upregulation of B7-1 and IL-12, resulting in conditions that maximally stimulate T cell activation and induction of T helper 1-type immune responses.